Western Medical Rehabilitation through Time: A Historical and Epistemological Review - Andrea A. Conti (The Scientific World Journal)
Medical rehabilitation is the process targeted to promote and facilitate the recovery from physical damage, psychological and mental disorders, and clinical disease. The history of medical rehabilitation is closely linked to the history of disability. In the ancient western world disabled subjects were excluded from social life. In ancient Greece disability was surmounted only by means of its complete removal, and given that disease was considered a punishment attributed by divinities to human beings because of their faults and sins, only a full physical, mental, and moral recovery could reinsert disabled subjects back in the society of “normal” people. In the Renaissance period, instead, general ideas functional for the prevention of diseases and the maintaining of health became increasingly technical notions, specifically targeted to rehabilitate disabled individuals. The history of medical rehabilitation is a fascinating journey through time, providing insights into many different branches of medicine. When modern rehabilitation emerges, around the middle of the twentieth century, it derives from a combination of management approaches focusing on the orthopaedic and biomechanical understanding of patterns of movement, on the mastering of neuropsychological mechanisms, and on the awareness of the social-occupational dimension of everyday reality.